Relationship between contrast sensitivity and corneal shape following overnight orthokeratology - Li-Li Liu; Li-Ping Gong; Yue-Yuan Xu; Xuan Zhu; Kaddie Kwok Chen; Wei-Feng Liu (International Journal of Ophthalmology, 2019)
AIM: To evaluate the relationship between contrast sensitivity (CS) and corneal shape following overnight orthokeratology (OK). METHODS: We conducted a retrospective clinical study of 80 lens-wearing myopia patients, all of whom had undergone OK and had been evaluated by Orbscan II topography. We measured the surface irregularity index (SIRI) of corneal topography at 3 and 5 mm, the size of the flattened central corneal curvature of OK lens (zone A), the size of the cornea altered by OK lens (zone B), the size of the pupillary area at the corneal level (zone C), the area of crossover between zones A and C (zone AC), the area of crossover between zones B and C (BC), the ratio of BC to B (BC/B), and the ratio of AC to C (AC/C). CS was evaluated using the CSV-1000 with spatial frequencies of 3, 6, 12, and 18 cycles/degree (CPD). RESULTS: Multiple correlation analyses indicated significant negative correlations between CS, zone C, BC/B, and 3-mm SIRI (all P<0.01). There were no significant differences between CS, zone B, AC/A, or 5-mm SIRI (P=0.60, 0.94 and 0.11, respectively). Zone C was negatively correlated with 3, 6, 12, and 18 CPD. 5-mm SIRI were negatively correlated with 6, 12, and 18 CPD. BC/C was negatively correlated with 6 and 18 CPD. AC/C was positively correlated with 3 CPD. CONCLUSION: Zone C, 3-mm SIRI and BC/B affect the CS following overnight OK.